(6х+4)/7 + (9-5х)/6 = (х-2)
Приводим обе части уравнения к общему знаменателю 42
(6х + 4) · 6 + (9 - 5х) · 7 = (х - 2) · 6 · 7
36х + 24 + 63 - 35х = 42х - 84
36х - 35х - 42х = -84 - 24 - 63
-41х = -171
х = -171 : (-41)
х = 171/41
х = 4 целых 7/41
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
Проверка: (6 · 171/41 + 4)/7 + (9 - 5 · 171/41)/6 = 4 7/41 - 2
(1026/41 + 4)/7 + (9 - 855/41)/6 = 2 7/41
29 1/41 : 7 - 11 35/41 : 6 = 2 7/41
1190/287 - 486/246 = 2 7/41
4 6/41 - 1 40/41 = 2 7/41
3 47/41 - 1 40/41 = 2 7/41
2 7/41 = 2 7/41 - верно
ответ: при х = 4 целых 7/41 выражения будут равны.
2)0,68*1,5=1,02
3) 61,71 : 1,02=60,5
4)63,163 :7,61=8,3
5) 60,5+8,3=68,8
Должно быть правильно...